Analisis Kebijakan Pemenuhan Kebutuhan Guru pada SMA di Kota Ambon - Rahabav, Williams Mauritz; Ratumanan, T.G.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
Teacher ratio in Maluku in general and Ambon City in particular still occur miss match good mismatch in meaning imbalance teacher to student ratio and mismatch in meaning not balance teacher competence with field tutored study. Problem the impact on the advantages of field teachers studies certain and happen shortage of teachers in other schools. Coping problem the issued SKB 5 Ministers. SKB 5 Ministers need follow up with Policy operations at the provincial level. As for the purpose study this that is 1) Knowing Policy Local Government in fulfillment the need for teachers at high schools in Ambon City; 2) Knowing burden teacher work at SMA in Ambon City; 3) Knowing school strategy in Fulfill burden teacher work at SMA in Ambon City and 4) Identify constraint school in Fulfill burden teacher work at a high school in Ambon City. Study this belong to study qualitative. Informant totaling 17 people with details: Head of GTK, 8 principals and 8 selected teachers with the purposive sampling technique data collection is done with use guidelines interview and study documentation. Data analysis was carried out with technique analysis descriptive quantitative and qualitative. The results of data analysis show that 1) Local Government Policy has Secrete two policy as explanation of the 5 Ministerial Decrees, namely: Regulations Maluku Governor (PERGUB) N0. 6, 2021 About Technical Instructions for Provision of Teachers No Permanent (GTT) and Honorary Teacher Salary Technical Guidelines School Assignments for 2022; 2) The ratio of high school teachers in Ambon City if compared with amount class / group obtained average of 1:19. However, if seen from comparison rombel with number of teachers per field study, happened imbalance ratio. In Ambon City happened the excess of teachers as many as 682 people and the shortage of teachers as many as -112 people; 3) all PNS teachers in Ambon City get reach a maximum of 24.53 JTM/ week and as many as 4 schools namely Alhilal Ambon High School, Mediatrix High School, Passo Christian High School and Maluku Adventist High School the civil servant teachers no reach 24 JTM / week; 4) Some the teacher 's problem is not reach JTM 24 Hours/ Week : (a) head school not enough pay attention to the activity decree addition to school for converted; many teachers are difficult for get additional JTM outside school, because the teacher must compete with other teachers; (c) school no could To do solving rombel because in accordance rule standard facilities and infrastructure as well as standard curriculum national governing amount burden Minimum and maximum teaching hours one week confirm that amount student maximum for high school is 20 students / group; (d) problem financial, fatigue result in delay go to school, teachers don't could complete Duty routine such as RPP and so on; (e) Number of lesson hours eye lesson certain in structure curriculum such as: English, foreign language others, history, art etc only 2 hours per week so the teacher doesn't could meet 18JTM/week as precondition and also not could Fulfill with Duty adjunct and teaching in other schools for reach 24 JTM / week.